2015
DOI: 10.21608/jhiph.2015.20247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Plantar Fasciitis among Patients with Heel Pain Attending Primary Health Care Centers of Makkah, Kingdom of Saudi Arabia

Abstract: Background: Plantar fasciitis is the most common cause of heel pain in adults seen in primary care. Extended standing and running frequently cause strain on the plantar fascia. Plantar fasciitis outcome is generally good, about 80 percent of people have no symptoms after one year. Objectives: To determine prevalence rate and risk factors of plantar fasciitis in primary health care settings. Methods: A cross-sectional study was conducted on 270 patients with heel pain attending five randomly selected primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…9 Previous studies have reported increased risk of plantar fasciitis with increasing BMI and showed positive association between these. 15,16 Contrary to this; current results did not reveal any significant association between BMI and PF.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…9 Previous studies have reported increased risk of plantar fasciitis with increasing BMI and showed positive association between these. 15,16 Contrary to this; current results did not reveal any significant association between BMI and PF.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are justified by the study conducted in Saudi Arabia by Goweda et al, documenting 1.72 times higher risk of plantar fasciitis with increasing age and it is most frequently found in middle age group of 40-60 years. 15 These findings are discordant with Alqahtani et al that reported higher percentages of plantar fasciitis among teachers of older age group with high load of teaching sessions. 9 Previous studies have reported increased risk of plantar fasciitis with increasing BMI and showed positive association between these.…”
Section: Discussionmentioning
confidence: 48%
“…Intrinsic factors are causative factors originating from within the body. 26 While extrinsic factors are causative factors arising from outside the body. Intrinsic factors include age, BMI, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of the US population complains of the incidence of pain in plantar fasciitis cases and results in one million professional visits for plantar fasciitis treatment each year. In the United States, plantar fasciitis accounts for more than 600,000 outpatients each year (Goweda, 2015). Based on data obtained from monthly reports at the medical rehabilitation clinic of the Bhakti Wira Tamtama Army Hospital, Semarang, Central Java, in 2017 there were 67 patients who experienced cases of plantar fasciitis from January to December 2018.…”
Section: Discussionmentioning
confidence: 99%
“…But in someone who has an abnormal foot, namely flat foot, it can occur at the age of less than 40 years old (Setyawan, 2016). The results of research conducted by Suzan stated that this plantar fasciitis accounts for 41.5% of problems in musculoskeletal cases in every tertiary care center in California, United States and has more than 600,000 outpatients each year (Goweda, 2015).…”
Section: Introductionmentioning
confidence: 99%